IMPLEMENTASI TPACK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR DI KABUPATEN TEGAL - Kurotul Aeni; Yuli Witanto; Noening Andrijati; Ika Ratnaningrum; Astuti, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low level of understanding of elementary school teachers in Tegal district, especially in Dukuhturi sub-district, regarding the use of technology in learning is a concern for all parties. This study aims to describe and analyze the implementation of TPACK in Pancasila education learning, obstacles and solutions. The research method is descriptive qualitative. The research subjects are elementary school teachers in Dukuhturi sub-district. Teknik pengumpulan data melalui wawancara dengan guru, observasi pada pembelajaran pendidikan Pancasila, dan dokumentasi. Keabsahan data menggunakan triangulasi sumber dan teknik. Data analysis includes data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that first, the implementation of TPACK in Pancasila education learning is applied through: 1) learning media such as canva, wordwall, quiziz, animated videos; 2) learning models, including: PBL, PjBL, Cooperative; 3) learning materials, including: getting to know the surrounding environment, norms, rights and obligations as citizens, mutual cooperation, Pancasila symbols and the sound of its principles, diversity; Second, the obstacles faced by teachers are inadequate facilities and infrastructure; limited knowledge and understanding of technology, requiring more time in learning. Third, the solution, teachers adjust to the existing facilities and infrastructure; teachers must learn again about TPACK; schools are expected to add technology-based facilities and infrastructure so that learning achieves its goals; teachers must be willing to learn with more competent colleagues; teachers must be able to manage time well when learning using technology.